The Relationship between Games, Creativity, and Numeracy Skills in Elementary School Students - Sabaruddin, Sabaruddin; Marzuki, Marzuki; Ulya, Khairatul; Saputra, Hendri (SCAD Independent, 2025)
Shifting from handcrafted to digital and factory-made toys has sparked worries about primary students’ fading creativity and numeracy skills. This mixed-methods study explores the relationship between children’s play and their creativity and numeracy achievements. The qualitative strand involved interviews with teachers and traditional toy artisans, capturing cultural practices, learning contexts, and observed skills during play. Qualitative results support these themes, showing that traditional play stimulates verbal interactions related to reasoning and problem-solving, particularly in spatial reasoning and mathematics. The quantitative results indicate that play frequency significantly predicts both creativity (β = 0.62, p < 0.001) and numeracy (β = 0.71, p < 0.001), explaining 78% and 86% of the variance, respectively. Traditional and modern non-digital games have positive effects, whereas digital games have significant negative effects. Path analysis further reveals a significant correlation between creativity and numeracy (r = 0.84, p < 0.001). Concerning the models that consider play type, the results show that traditional play consistently supports both outcomes. Digital play tends to exhibit negative impacts, and modern non-digital play contributes positively, albeit to a lesser extent. The tapestry of both data types deepens the conclusion that play, especially when culturally situated, nurtures cognitive development.